FASILITATOR KEREN DENGAN PILIHAN METODE DAN TEKNIK PEMBELAJARAN PADA PELATIHAN BAGI GENERASI MILENIAL - Supinah Supinah (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
This paper explains about cool facilitators using a choice of learning methods and techniques that are suitable and highly approved by participants in learners at training for the millennial generation. Learning methods and techniques that allow students to improve knowledge, skills and improve behavioral attitudes also make participants happy and useful. However, in the learning experience, some participants experienced unattractive and unpleasant conditions for the methods and techniques used by the facilitator in delivering the training subject material. This will affect the participants' interest in broadening and deepening their understanding of each training subject delivered in learning. Learning in training for the millennial generation has changed and developed along with the development of digital application-based Information and Technology (IT). This situation requires the application of learning methods and techniques that are suitable and highly approved to be applied in learning in training for the millennial generation. This paper aims to get a choice of learning methods and techniques that are most suitable and highly approved for use so that facilitators become cool in learning at training for the millennial generation. The benefits of this paper make it easier and easier for facilitators to use methods and techniques in learning in training for the millennial generation. This writing uses a qualitative research method that is explanatory by analyzing the collected data. The results of the discussion with the data processing method showed that the appropriate and highly approved learning methods and techniques to be applied in learning at training for the millennial generation were Discussion and Feedback; Active Interaction; Image and Graphics Technology; Be wise in answering questions; Question and answer method.